2006
DOI: 10.1159/000095787
|View full text |Cite
|
Sign up to set email alerts
|

Is Primary Hyperaldosteronism a Risk Factor for Aortic Dissection?

Abstract: Primary hyperaldosteronism is a rare (<1%) and underdiagnosed cause of secondary hypertension. We present a case of aortic dissection in a patient with primary hyperaldosteronism. To our knowledge, there are six other reported cases of aortic dissection in patients with primary hyperaldosteronism. Our case strengthens the hypothesis that primary hyperaldosteronism is a potential independent risk factor for aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…However, aortic dissection has been demonstrated in patients with primary aldosteronism. 9 In addition, patients with glucocorticoid-remediable aldosteronism, an inherited form of primary hyperaldosteronism, often die at a young age due to rupture of cerebral aneurysms. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, aortic dissection has been demonstrated in patients with primary aldosteronism. 9 In addition, patients with glucocorticoid-remediable aldosteronism, an inherited form of primary hyperaldosteronism, often die at a young age due to rupture of cerebral aneurysms. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In a clinical case report, aortic dissection was found in patients with primary aldosteronism (also known as hyperaldosteronism). 9 In addition, an analysis of drug modulation of AAA growth through 25 years of surveillance in 1,269 patients demonstrated a strong association between mineralocorticoid receptor blockers and slowed AAA progression. 10 However, a cause and effect relationship between the mineralocorticoid receptor and aortic aneurysms has not been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Primary aldosteronism is a curable form of secondary hypertension, and the incidence of primary aldosteronism among hypertensives is higher than previously reported 5) . It has been reported that aldosterone plays a crucial role in the development of damaged organs following heart failure, fibrotic changes in blood vessels, and renal failure 7) , and that primary hyperaldosteronism is a potential independent risk factor for aortic dissection 8) . There are several reports of patients with primary aldosteronism, which caused dissecting aortic aneurysm 9,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone may affect the matrix metalloproteinases and their inhibitors, leading to collagen degradation and subsequent medial necrosis [4]. Aldosterone may activate the adventitia, resulting in proliferation and migration of fibroblast and secretion of collagen to exacerbate vascular remodeling [11].…”
Section: Discussionmentioning
confidence: 99%